2006
DOI: 10.1093/eurheartj/ehi835
|View full text |Cite
|
Sign up to set email alerts
|

Urban air pollution and emergency admissions for cerebrovascular diseases in Taipei, Taiwan

Abstract: Emergency admissions for cerebrovascular diseases among adults were positively associated with increasing urban air pollution levels of O(3) lagged 0 day and CO lagged 2 days in Taipei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 33 publications
3
88
0
1
Order By: Relevance
“…Possible links between air pollution, particularly that caused by atmospheric particles and SO 2 , and the number of hospital admissions have been recently established in studies from North America, [3][4][5][6][7][8][9][10][11][12] South America, [13][14][15][16] Asia, [17][18][19][20][21][22] Australia 22 and Europe. [23][24][25][26][27][28][29][30][31][32][33][34][35] However, there are still many aspects to elucidate the causal relationships between air pollution and physical condition, such as the separation of the short-term and long-term health effects of individual air pollutants and those of complex pollutant mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Possible links between air pollution, particularly that caused by atmospheric particles and SO 2 , and the number of hospital admissions have been recently established in studies from North America, [3][4][5][6][7][8][9][10][11][12] South America, [13][14][15][16] Asia, [17][18][19][20][21][22] Australia 22 and Europe. [23][24][25][26][27][28][29][30][31][32][33][34][35] However, there are still many aspects to elucidate the causal relationships between air pollution and physical condition, such as the separation of the short-term and long-term health effects of individual air pollutants and those of complex pollutant mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ACUTE EFFECTS OF PARTICULATE MATTER EXPOSURE Although most studies on PM and cardiovascular diseases have been conducted in developed western countries, first impulses for epidemiologic research on IS came from South Korea and Taiwan. 15,22,25 An increase in PM by an interquartile range in Seoul was associated with a 3% higher IS mortality. 25 Furthermore, the same increase in PM exposure resulted in a statistically significant increase in the hospitalization rate due to IS in Kaohsiung (Taiwan) of 46%.…”
Section: Particulate Matter and Human Health Particulate Matter Is A mentioning
confidence: 99%
“…Studies have shown that for each increase in PM 2.5 mass concentration by 10 µg m -3 , all-cause mortality increased by 1.4, 1.5, 2.7, and # These authors contributed equally to this work. 0.8% in Barcelona, Stockholm, Madrid, and the Netherlands, respectively (Mate et al, 2010;Guaita et al, 2011;Ostro et al, 2011;Tobías et al, 2011;Meister et al, 2012), mainly because of the harm from the air pollutants to the cardiovascular and respiratory systems (Chan et al, 2006;Jimenez et al, 2009;Guo et al, 2010;Jimenez et al, 2010;Tsai et al, 2010;Yu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%